Dynamics of plasma membrane surface related to the release of extracellular vesicles by mesenchymal stem cells in culture - Santiago Casado (Nature Portfolio, 2017)
Abstract Extracellular vesicles (exosomes and shedding vesicles) released by mesenchymal stem cells (MSCs) are regarded as a storable, cell-free alternative with comparable therapeutic potential to their parent cells. Shedding vesicles originate as bulges on the cell surface but little is known about their turnover or how their formation can be stimulated. We have used atomic force microscopy (AFM) to follow the formation dynamics of bulges in living adipose tissue-derived MSCs. AFM images showed that, in general, MSCs present hundreds of nanosized protrusions on their surface with life spans of 10–20 min. Scanning electron microscopy confirmed those images and showed that bulges are also formed on filamentous processes. Extracellular vesicles deposited on the culture surface have comparable sizes to those of bulges showing up on the cell surface. The amount of protrusions on cells treated with progesterone or PDGF-BB, two treatments that stimulate the secretion of extracellular vesicles in MSCs, was evaluated by AFM. Measurements of the cross-area at 50 nm over the cell surface provided estimates of the amount of protrusions and showed that these values increased with the stimulating treatments. Our study suggests that shedding vesicles constitute a large population of the extracellular vesicle pool.